Studi Morfologi Polen Tanaman Pekarangan Di Perumahan Gn. Dubbs Balikpapan - Palupi, Elok; syafrizal, Syafrizal; Hariani, Nova (BIOPROSPEK: Jurnal Ilmiah Biologi, 2018)
This research was conducted to determine the morphology of pollen from the type of yard plants found in Gn. Dubbs street Balikpapan. The method used is the method making preparations for the acetolysis pollen. The result of this research obtained 9 spesies and 9 types of family are Allamanda cathartica (famili Apocynaceae), Europhibia milii (famili Euphorbiaceae), Caesalpinia pulcherrima (famili Fabaceae), Orthosiphon stamineus (famili Laminaceae), Hibiscus rosa-sinensis (famili Malvaceae), Muntingia calabura (famili Elaeocarpaceae), Mirabilis jalapa dan Bougainvillea sp. (famili Nyctaginaceae), Ixora sp. (famili Rubiaceae). Pollen morphology of plant traits found in residential lawns Gn.Dubbs Street is the type aperture (inaperture, periporalate, syncolpatae, monoporalate, diporalae, tricolpalate and stephanocolpate), from additional (reticulate, baculate, striate, verrucate, regulate dan scabrate)